Geometrical study of mixed adhesive joints for high-temperature applications - Marques, E. A. S. (2016)
The use of adhesives for high-performance structural applications has significantly increased in the last decades. However, the use of adhesive joints in adverse environmental conditions is still limited due to the reduced capability of adhesives to withstand large thermal gradients. Dual adhesive joints, which contain two adhesives with remarkably different mechanical behaviours, are a technique suitable for being used in extreme temperatures. The object of this study is a ceramic–metal joint, representative of the thermal protection systems of some aerospace vehicles. In this paper, several joint-mixed joint geometries are presented, studied with recourse to finite element analysis. In a first phase, the three-dimensional finite element models and the material properties are validated against experimental data. In a second phase, the model geometry is modified, with the aim of understanding the effect of several changes in the joints’ mechanical behaviour and comparing the merits of each geometry. The models’ presented good agreement was found between experimental and numerical data and the alternative geometries allowed the introduction of additional flexibility on the joint but at the cost of lower failure load.